PENENTUAN PRODUK OLAHAN APEL UNGGULAN MENGGUNAKAN TEKNIK FUZZY NON NUMERIK AN ANALISIS STRUKTUR SERTA POLA PEMBINAAN KELEMBAGAAN [Determination Prosprctive Appe processing product Using Non-Numeric Fuzzy Method, Analyze Institutional Structure and Develo - Imam Santoso; Marimin , (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2001)
Apple and its processing product is one of prospective commodities in Malang, East Java. The article discussed application of fuzzy non-numerik decision making to select prospective apple processing product, analyse institutional structure using ISM method and determine development model using AHP method. The research result showed apple dodol selected as the most prospective product with high category elements of entrepreneur, corporation, and high ediare as independent elements; and partnership (46%) selected as model of institutional estabilishment.